PENGARUH HUMAN CAPITAL DAN MARKETING CAPABILITY TERHADAP KINERJA KEUANGAN DAN NILAI PASAR (STUDI KASUS PADA SEKTOR BARANG KONSUMSI) - Fonny Agustina Pangestu; Sarce Elsye Hatane (Business Accounting Review, 2016)
This Study aimed to examine the affect of human capital and marketing capabilities to financial performance and market value. Return on equity represented the profitability, while Market to Book Value represented the market value. Human Capital Efficiency represented human capital, and marketing ratio represented marketing capabilities, while company size and company age were control variables to explain the relationship of marketing capabilities and profitability and market value. Data used in this study were secondary data from the company’s annual report. This study used 29 companies in the sector of food and beverage industry which listed in Indonesian Stock Exchange from 2009 until 2014 by using purposive sampling method. Hypotheses in the study analysed by using multiple regression method. The result showed that Human Capital had positive affect on profitability and negative affect to the market value, Marketing Capabilities had negative affect on profitability and market value, company age had positive affect on profitability and did not affect the market value, and the company size had no influence on profitability and market value.